The Effect Of Roblox Application On 7th-Grade Students’ Vocabulary Mastery - Hasani, Elsya Elita Merlyn; Sinaga, Nenni Triana; Lestari, Febrika Dwi (PIJAR: Jurnal Pendidikan dan Pengajaran, 2025)
This study investigates the effect of the Roblox application on the English vocabulary mastery of seventh-grade students at SMP Negeri 37 Medan. The research was motivated by students’ limited vocabulary acquisition, which often hampers their communication skills, as well as the lack of digital integration in conventional teaching methods. A quantitative method with a true experimental design was employed, involving two classes as samples: class 7-A (31 students) as the experimental group taught using the Roblox application and class 7-B (31 students) as the control group taught conventionally. The research instruments consisted of vocabulary tests including multiple-choice, word-matching, and fill-in-the-blank tasks, administered as pre-tests and post-tests. The findings revealed that the experimental group achieved a higher mean score improvement, increasing from 64.84 to 78.55, compared to the control group, which only improved from 63.38 to 71.61. Statistical analysis using an independent t-test (t-value 2.516 > t-table 2.000, α=0.05) confirmed a significant difference between the groups with a medium effect size (0.39). These results indicate that the Roblox application positively influences students’ vocabulary mastery and can serve as an effective supplementary tool for English language teaching at the junior high school level